Augmentative Releases of Two Diachasmimorpha longicaudata (Hymenoptera: Braconidae) Population Lines Under Field-Cage Conditions to Control Ceratitis capitata (Diptera: Tephritidae) - Buonocore Biancheri, María Josefina (2022)
Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), known as Medfly, is a severe agricultural invasive pest in Argentinian fruit-producing regions. The native habitat disturbance and introduction and spread of exotic host plants strongly favored Medfly proliferation. This scenario is common throughout the northern subtropical citrus-growing region. Environmentally friendly strategies to suppress Medfly populations by the National Fruit Fly Control and Eradication Program have currently been taken. One of these actions involves augmentative biological control through releases of the exotic parasitoid Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae). Consequently, the hypothesis that the effectiveness of D. longicaudata females, from two different population lines, in controlling Medfly larvae progressively increases as the density of released females increases was tested. One parasitoid line derives from larvae of a biparental Medfly strain. The other hails from irradiated larvae of the genetic sexing Temperature Sensitive Lethal Vienna-8 medfly strain reared at the “BioPlanta San Juan” biofactory. Parasitoids foraged for 24 h on peaches artificially inoculated with naked lab-reared biparental Medfly larvae. Peaches were placed near the roof or on the ground in field cages. Five treatments (20, 40, 80, 160, and 320 females released) and a control (no parasitoids) for each population line were carried out throughout summer and autumn 2016. Host density (200 larvae) remained constant. At 320 released parasitoid females, both D. longicaudata population lines highly increased the Medfly mortality in both testing seasons, and foraged skillfully on peaches at both fruit height levels. These data encourage the application of augmentative biological control against Medfly.